Influence of chemotherapy to hormonal levels in postmenopausal breast cancer patients - Přibylová, Olga; Springer, Drahomíra; Svobodník, Adam; Kýr, Michal; Zima, Tomáš; Petruželka, Luboš (Neoplasma, 2008)
Targeting and tailoring of therapy is the latest trend in breast cancer treatment. The efficacy of the available treatment must be estimated and the probable benefit for the patient determined. The aim of this project was to find out wether also in postmenopausal women chemotherapy can affect hormonal levels in serum and if even the levels of IGF-1 and IGFBP-3 can be changed. In the group of 72 postmenopausal breast cancer patients blood samples were taken before, during and after adjuvant chemotherapy and levels of estradiol, progesterone, LH, FSH, IGF-1 and IGFBP-3 were evaluated. We did not find any statistically significant dependence on tumor stage, expression of hormonal receptors or HER-2 and treatment regimen with studied hormones. Serum levels before treatment in comparison with status during treatment were significantly different in LH, FSH and progesterone value. Hormone levels after the treatment in comparison with status during treatment were significantly different only in levels of estradiol. Significant differences in all parameters were found except IGF-1. There was not any statistical dependence on the menopausal gap, age, weight or type of chemotherapy. We can conclude, that also in postmenopausal women hormonal changes can take part in the final effect of adjuvant treatment.
Keywords: Postmenopause; senioři nad 80 let; insulinu podobný růstový faktor I; nádory prsu; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; lidé středního věku; Carcinoma, Ductal, Breast; Aged, 80 and over; Middle Aged; Financing, Organized; postmenopauza; Breast Neoplasms; Chemotherapy, Adjuvant; financování organizované; Estrogens; Follicle Stimulating Hormone; progesteron; Insulin-Like Growth Factor I; estrogeny; duktální karcinom prsu; Estradiol; ženské pohlaví; luteinizační hormon; lidé; adjuvantní chemoterapie; estradiol; Progesterone; Aged; senioři; folikuly stimulující hormon; Luteinizing Hormone; Female